Network Analysis of the Association between Minority Stress and Activism in LGB People from Poland - Aleksandra Krok; Zofia Kardasz; Aleksandra M. Rogowska (MDPI AG, 2024)
(1) Background: This paper presents an analysis of the associations between minority stressors and activism in the population of lesbian, gay, and bisexual individuals in Poland. (2) Methods: The cross-sectional online-based research was conducted among 192 lesbian, gay, and bisexual (LGB) people in two groups: activists (n = 51) and people not engaged in activism (n = 141). Four scales of the Sexual Minority Stress Scale were used: Internalized Homophobia, Expectation of Rejection, Concealment, and Sexual Minority Negative Events Scale. Activism was measured using the Activism Scale and a single item asking about belonging to an activist group. (3) Results: Activists, lesbians, and gays scored significantly higher in the Sexual Minority Negative Events than people not involved in activism and bisexual individuals. Attitude toward LGBT+ activism correlated weakly and positively with Sexual Minority Negative Events and Expectation of Rejection while negatively with Internalized Homophobia. The Network Analysis showed that positive attitudes toward LGBT+ activism, the expectation of rejection, and negative events in minority stress are the most influential variables in the network model, playing a crucial role in the interaction between particular dimensions of minority stress. (4) Conclusions: Prevention and intervention programs should focus on reducing minority stress, especially negative events and rejection, especially among lesbians, gays, and people engaged in LGBT+ activism. The cooperation of politicians, lawyers, social workers, and psychologists is required to decrease homophobia and the stigmatization of people representing sexual and gender minorities.